Integrated genomics provides insights into the evolution of the polyphosphate accumulation trait of Ca. Accumulibacter - Xie, Xiaojing (2024)
Candidatus Accumulibacter, a prominent polyphosphate-accumulating organism (PAO) in wastewater treatment, plays a crucial role in enhanced biological phosphorus removal (EBPR). The genetic underpinnings of its polyphosphate accumulation capabilities, however, remain largely unknown. Here, we conducted a comprehensive genomic analysis of Ca. Accumulibacter-PAOs and their relatives within the Rhodocyclaceae family, identifying 124 core genes acquired via horizontal gene transfer (HGT) at its least common ancestor. Metatranscriptomic analysis of an enrichment culture of Ca. Accumulibacter revealed active transcription of 44 of these genes during an EBPR cycle, notably including the polyphosphate kinase 2 (PPK2) gene instead of the commonly recognized polyphosphate kinase 1 (PPK1) gene. Intriguingly, the phosphate regulon (Pho) genes showed minimal transcriptions, pointing to a distinctive fact of Pho dysregulation, where PhoU, the phosphate signaling complex protein, was not regulating the high-affinity phosphate transport (Pst) system, resulting in continuous phosphate uptake. To prevent phosphate toxicity, Ca. Accumulibacter utilized the laterally acquired PPK2 to condense phosphate into polyphosphate, resulting in the polyphosphate-accumulating feature. This study provides novel insights into the evolutionary emergence of the polyphosphate-accumulating trait in Ca. Accumulibacter, offering potential advancements in understanding the PAO phenotype in the EBPR process.